PRAKTIK PERJANJIAN NOMINEE DI SEKTOR PARIWISATA - Putri Kusuma Sanjiwani (Jurnal Ilmiah Hospitality Management, 2017)
This study entitled "Practice of Nominee Agreements in The Tourism Sector". This research was motivated by the development of enterprises providing accommodation very rapidly evolved in Bali. Sample used is the development of enterprises providing accommodation in Ubud Tourism Village. Management system kinship turned into a professional management due to the influx of foreign businessmen as an investor. Foreign entrepreneurs have the mission as a tenant of accommodation and practices nominee agreement. Foreign entrepreneurs as foreign investors borrowed the name of an Indonesian citizen (citizen) to rent an accommodation and the accommodation is not used in private but more commercialized on behalf citizen of Indonesia. This study uses normative research and analyze the problems with the theory of the state law, the theory of the agreement, the concept of tourism and the principle of freedom of contract in dissecting the problems. The results of this study indicate that the validity of a nominee agreement is still not regulated in the legislation and is a commonly used smuggling law in passing foreign businessmen in investing.